Pengaruh Kualitas Produk Terhadap Keputusan Pembelian: Kepercayaan Sebagai Variabel Mediasi (Studi Kasus Eyeshadow Pinkflash) - Helviani Rifdah Nazwa; Rahyuniati Setiawan; Wufron (POLITEKNIK LP3I, 2026)
This study uses a case study of Pinkflash Eyeshadow in the Indonesian market to assess the influence of product quality on consumer purchase decisions by looking at trust mediation. Using primary data gathered from a survey of 189 respondents who had performed one transaction, this study employs an expsplanatory quantitative methodology. The data was analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The findings demonstrated that product quality had a favorable and significant impact on purchasing decisions. Furthermore, high-quality products significantly increase consumer trust, which has a significant impact on purchasing decisions. Mediation testing indicates that consumer trust plays a role in mediating the relationship between product quality and purchasing decisions. This suggests that Effectiveness product quality in facilitating transactions is not only determined by product specifications, but also through product's ability to foster consumer trust. This study offers theoretical contributions to enhance the integration of consumer behavior and marketing perspectives, as well as practical implications for businesses in developing product strategies focused on maintaining a positive reputation and fostering trust.